2009
DOI: 10.1007/s11738-009-0332-1
|View full text |Cite
|
Sign up to set email alerts
|

Plant regeneration from carrot (Daucus carota L.) anther culture derived embryos

Abstract: The research concerned of the regeneration of plants from embryos obtained from anther cultures of seven carrot (Daucus carota L.) cultivars. The aim was to determine the influence of the regeneration medium on the efficiency of the regeneration process. The optimization of the adaptation of the obtained plants was also carried out. Embryogenesis occurred on four of the tested media: B5 and MS without hormones, MS with charcoal, and MS with 1 mg dm -3 BA and 0.001 mg dm -3 NAA. Embryos obtained from the anther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
(26 reference statements)
0
8
0
1
Order By: Relevance
“…However, the majority of embryos were formed after 3-4 weeks of culture. Górecka et al [21] reported that embryos appeared after 2 weeks from the onset of an experiment, and their formation was observed until the third month. In isolated microspore cultures, the appearance of the first structures was recorded after 2 weeks, but they were not yet visible to the naked eye.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the majority of embryos were formed after 3-4 weeks of culture. Górecka et al [21] reported that embryos appeared after 2 weeks from the onset of an experiment, and their formation was observed until the third month. In isolated microspore cultures, the appearance of the first structures was recorded after 2 weeks, but they were not yet visible to the naked eye.…”
Section: Discussionmentioning
confidence: 99%
“…Plant regeneration and acclimatization were conducted according to the method described by Górecka et al [21]. When embryos in flasks ( Fig.…”
Section: Regeneration and Acclimatization Of Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the list of cultivated species that have originated from haploids derived through in vitro androgenesis includes barley [58], wheat [59], rape [62], carrot [65][66][67], cucumber [68] and cabbage [69]. Production of embryos from female gametophyte cells via apogamy or parthenogenesis ensures stability of DH lines (while retaining a low rate of albinism).…”
Section: Haploids and Double Haploid Plantsmentioning
confidence: 99%
“…Medium composition has been identified as a key factor influencing initial callus induction and subsequent plant regeneration in some model plants such as cereal crops and brassica (Keller at al., 1975;Chen et al, 2005;Gorecka et al, 2009). An auxin has been reported to be absolutely required to initiate and promote microspore embryogenesis and a small amount of cytokinin in addition to auxin improves the yield of embryoids in anther culture of oilseed rape (Loh and Ingram, 1982).…”
Section: Introductionmentioning
confidence: 99%